3D bioprinting for reconstructive surgery: Principles, applications and challenges. Issue 9 (September 2017) - Jessop, Zita M.; Al-Sabah, Ayesha; Gardiner, Matthew D.; Combellack, Emman; Hawkins, Karl; Whitaker, Iain S.
Summary: Despite the increasing laboratory research in the growing field of 3D bioprinting, there are few reports of successful translation into surgical practice. This review outlines the principles of 3D bioprinting including software and hardware processes, biocompatible technological platforms and suitable bioinks. The advantages of 3D bioprinting over traditional tissue engineering techniques in assembling cells, biomaterials and biomolecules in a spatially controlled manner to reproduce native tissue macro-, micro- and nanoarchitectures are discussed, together with an overview of current progress in bioprinting tissue types relevant for plastic and reconstructive surgery. If successful, this platform technology has the potential to biomanufacture autologous tissue for reconstruction, obviating the need for donor sites or immunosuppression. The biological, technological and regulatory challenges are highlighted, with strategies to overcome these challenges by using an integrated approach from the fields of engineering, biomaterial science, cell biology and reconstructive microsurgery.